The Impact of Servant Leadership on Organizational Performance: The Mediating Role of Affective Commitment and Organizational Citizenship Behavior - Salud, Jr., Calixto (Archīum Ateneo, 2021)
This study examined the mediating role of affective commitment and organizational citizenship behavior on the impact of servant leadership on organizational performance. An electronic survey was sent to 395 participants who responded to a 25-item instrument covering the four constructs of servant leadership (SL), affective commitment (AC), organizational citizenship behavior (OCB) and organizational performance (OP). Using structural equation modelling to analyze the mediation model, the study showed that AC and OCB mediated the impact of SL on OP and that SL was positively linked to AC, OCB, and OP. As a whole the four constructs formed a new model as described.